FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU WUS DALAM DETEKSI DINI KANKER SERVIKS DI KELURAHAN DWIKORA MEDAN TAHUN 2014 - Fridalina Tarigan (UNIVERSITAS SARI MUTIARA INDONESIA, 2016)
Cervical cancer is a health problem that hit the countries in the world, including in Indonesia. The number of cervical cancer ranks first in the illness of women in the state developments. Cervix or uterus cancer is the number one cause which is common in women. However, information on this subject has not been widely known as cervical cancer does not cause symptoms or complaints that women come to the doctor in the condition that it was too late. Risk factor for cervical cancer is sexual behavior, smoking, trauma chronic cervical, oral contraceptives in the long term, socio-economic strata low, low education, early marriage, customs hugiene sex is not good, high parity and income is not fixed , This study aims to determine the factors that berhungan with WUS behavior in the early detection of cervical cancer in the Village Dwikora 2014 This type of research is analytic survey with cross sectional design approach. The population is all WUS aged 30-50 years who live in the environment 2, 6, 8, 9 in the Village Dwikora. Samples were 110 people with purposive sampling technique. Data analysis Chi Square and unconditional logistic regression. The results showed that age (p = 0.048), education (p = 0.124), occupation (p = 0,142), knowledge (p = 0.039), recommended by health care workers (p = 0.168) had a significant relationship with the behavior of WUS for early detection cervical cancer. While the support of husband / family no effect. The most dominant variable related to the behavior of cervical cancer detection attitude (p = 0.002). Suggested to health workers in Sub Dwikora improve service activities, in particular about the early detection of cervical cancer and counseling on early detection of cervical cancer in order to improve the behavior of WUS in the early detection of cervical cancer and provide rewards to health centers service coverage showed improvement and is able to achieve the target determined.Keywords: Behavior, womanof fertile age, Early Detection, Cervical Cancer